Stocking rate, supplementation and implants for steers grazing bluestem pasture in early summer - Held, R.; Smith, E.F.; Riley, Jack G.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2010)
Native bluestem pastures were grazed from May 10 to July 15, 1982 by steers averaging 599 lbs, at stocking rates 1.82, 1.5, 1.2 acres per steer. Daily gains were similar for all rates, but gain per acre increased with increased stocking rate. Half of the steers were self-fed a salt-limiting sorghum grain-Rumensin® mixture, at about 1.8lb per steer per day. Supplementation increased daily gain (P<.05) but actual differences were small (2.08 vs. 1.91 lb per day). Gain per acre was increased 7 lbs by supplementation. Herbage yields at mid-July were least on the heavily stocked pastures, but by October regrowth on all pasture was equal. Stocking rate did not affect botanical composition. There were no significant gain differences for steers implanted with either Compudose®, Ralgro® or Synovex®, even though 24 percent of the Compudose implants were lost by mid-summer.
Keywords: Beef; Stocking rate; Supplementation; Implants; Bluestem